Glanuloplasty with Oral Mucosa Graft following Total Glans Penis Amputation - Kwaku Appiah; George Amoah; Roland Azorliade; Kofi Gyasi-Sarpong; Ken Aboah; Douglas Arthur; Baah Nyamekye; Kwaku Otu-Boateng; Patrick Maison; Benjamin Twumasi-Frimpong; Issac Opoku Antwi; Edwin Yenli (Case Reports in Urology)
This is a report on the technique of neoglans reconstruction in a patient with amputated glans penis following guillotine neonatal circumcision. A 4 cm long and 2 cm wide lower lip oral mucosa graft was harvested and used to graft the distal 2 cm of the corporal bodies after 2 cm of the distal penile skin had been excised. One edge of the lower lip oral mucosa graft was anastomosed to the urethral margins distally and proximally to the skin. At six months of followup, patient had both satisfactory cosmetic and functional outcomes.